PENGARUH EKUIVALEN NISBAH BAGI HASIL TABUNGAN, NISBAH BAGI HASIL DEPOSITO DAN FREKUENSI PENCAIRAN PEMBIAYAAN MURABAHAH TERHADAP JUMLAH NASABAH BARU PADA BMT AS-SALAM KRAS KEDIRI - Ulfa, Nur Aini (IAIN Tulungagung, 2016)
The research aim is to investigate the equivalent effect of proft sharing ratio of savings, proft sharing ratio of deposits, and the frequency of murabaha fnancing disbursement to the addition of new customers in BMT As- Salam Kras Kediri. The analysis method of the research is multiple regression linier. The results of the research indicated that equivalent of proft sharing ratio of savings and equivalent of proft sharing ratio of deposits have positive effect but not signifcant on the addition of new customers. Frequency of murabaha fnancing disbursement has positive and signifcant effect on the addition of new customers. And together 3 variables above showed a signifcant effect on the addition of new customers in BMT As- Salam Kras Kediri.Keyword: equivalent of proft sharing ratio of savings, proft sharing ratio of deposits, frequency of murabaha fnancing disbursement